Teaching research: a programme to develop research capacity in undergraduate medical students at the University of KwaZulu-Natal, South Africa - Knight, Stephen E. (BMC Med Educ, 2016)
BACKGROUND: Improved research ability is a core competency to achieve in health professionals. The Selectives is a three-year, longitudinal, community-based programme within the undergraduate curriculum which aims to develop research capacity in all medical students during the prescribed curriculum. In relation to the programme, the authors describe the types of studies conducted by students, conditions that facilitated their learning, how the experience improved students’ knowledge of research and public health and their development of reflective learning practices. METHODS: A cohort of 212 students completed the Selectives Programme in 2014, and 69 (32 %) completed an anonymous online evaluation thereafter. Data collected include students’ perceptions of the research component of Selectives; its impact on their knowledge of research and a documentary analysis of their research protocols and posters. Ethical approval for the ongoing evaluation of the Selectives was sought and obtained from the institutional Biomedical Research Ethics Committee. RESULTS: During Selectives, 75 groups of 2–4 students conducted research studies of primary health care problems in community settings. Each group is assessed on their presentation of research findings as a scientific poster. The Selectives facilitated learning for the majority of the cohort. Students reported positive learning experiences about the research process, including ethics; protocol writing; data processing; dissemination of findings and results; and their use in informing a health promotion intervention. Students reported having gained a better understanding of their strengths and weaknesses through reflective learning from this academic activity. The Selectives is scheduled adjacent to the students’ mid-year vacation. This scheduling together with the placement in the students’ home community minimizes travel and accommodation costs associated with working outside the academic teaching platform and therefore makes it a cost-effective model in a low resource context. CONCLUSIONS: The Selectives has proven beneficial to develop a range of generic and practical research competencies for a full cohort of students enrolled in the undergraduate medical curriculum. The Selectives research process is integrated with learning about population health and the social determinants of health in a primary health care setting. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-016-0567-7) contains supplementary material, which is available to authorized users.